An integration of AHP-ACO technique for social interaction and travel planning - Peh, Perly Thai Ee (2016)
The current web and mobile computing technologies have encouraged all sorts of applications mushroom in the market. However, most of the application that available does not integrate the place recommendation and route planning. Besides that, improving the processing speed of the algorithm is also another challenge of this research. Thus, the objectives of this research is to integrate the place recommendation based on profile preference using Analytic Hierarchy Process (AHP) method and route planning using ACO method. The second objective of this research is to enhance the processing speed of the proposed AHP-ACO technique in generating the optimum route plan. This study presents the integration methods of AHP algorithm for point of interest decision-making and ACO and rule-based algorithms for route optimization. AHP interest scores based on user preferences, business information and community reviews are used to model decision making. ACO and rule-based algorithms are used to arrange the itinerary of the place of interest that either has been chosen by the user or recommended by the system.The integration AHP-ACO method has been enhanced to reduce the execution time from 5 minutes to 30 seconds for 7 days trip planning. Object Oriented Software Engineering(OOSE) methodology has been used to build the mobile recommender system prototype and web application prototype. Questionnaires have been distributed to collect user feedback. The results show that the integration method is promising for helping the user in making decisions and itinerary arrangements.